2022
DOI: 10.1093/ajcn/nqab379
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc-biofortified rice on zinc status of Bangladeshi preschool children: a randomized, double-masked, household-based, controlled trial

Abstract: Background Zinc biofortification of rice could sustainably improve zinc status in countries where zinc deficiency is common and rice is a staple, but its efficacy has not been tested. Fatty acid desaturases (FADS) are putative new zinc status biomarkers. Objective Our objective was to test the efficacy of zinc-biofortified rice in preschool-aged children with zinc-deficiency. Our hypothesis was that consumption of zinc-biofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…No association of serum Zn with dietary or supplemental Zn intakes was seen in the NHANES study even though 8% of participants had serum Zn levels below the cut-off for Zn deficiency ( 14 ). No changes in PZC were seen after the consumption of Zn biofortified grains and foods either in children or adults ( 15 18 ). Additionally, PZC does not respond to short-term exposure to Zn fortified foods.…”
Section: Plasma/serum Zn Concentrations–the Best Available and Accept...mentioning
confidence: 97%
See 1 more Smart Citation
“…No association of serum Zn with dietary or supplemental Zn intakes was seen in the NHANES study even though 8% of participants had serum Zn levels below the cut-off for Zn deficiency ( 14 ). No changes in PZC were seen after the consumption of Zn biofortified grains and foods either in children or adults ( 15 18 ). Additionally, PZC does not respond to short-term exposure to Zn fortified foods.…”
Section: Plasma/serum Zn Concentrations–the Best Available and Accept...mentioning
confidence: 97%
“…A recent double-blind randomized controlled trial found no changes in FADS1 nor FADS2 activities in Bangladeshi preschool children, fed Zn biofortified rice diets (providing 1 mg of Zn/day) for 9 months ( 18 ). Several reasons might explain the lack of interaction between desaturases activity and dietary Zn intake.…”
Section: Human Studies–uncontrolled Nutrient (Dietary) Intervention A...mentioning
confidence: 99%
“…Plasma fatty acid concentrations, and estimates of fatty acid desaturase activities, based on the ratios of product to precursor omega-6 fatty acids, have been identified as novel biomarkers of zinc status due to a strong correlation with plasma zinc concentrations [ 59 , 60 ]. Additionally, zinc may be more efficiently directed towards fatty acid desaturation when taken with food compared with zinc taken in the fasted state [ 49 ].…”
Section: Zinc Utilization and Trends In Zinc Biomarkers For Monitorin...mentioning
confidence: 99%
“…Compared with post-harvest fortification, the lack of a need for special processing reduces the cost of biofortification after the initial crop development. Recent crops targeted for zinc biofortification include wheat [ 36 , 79 , 80 ], rice [ 60 , 81 , 82 ], maize [ 27 , 83 ], pearl millet [ 25 , 84 ], beans [ 43 , 85 ], and bananas [ 86 ].…”
Section: Trends In Zinc Fortification Strategiesmentioning
confidence: 99%
“…A limited number of studies have tested the efficacy and effectiveness of Zn agronomically biofortified cereal flours for improving human Zn status ( 29 31 ). While dietary Zn intakes were increased, there is mixed evidence on the effect on biomarkers of Zn status.…”
Section: Introductionmentioning
confidence: 99%